Efficient and secure opto-cryptosystem for color images using 2D logistic-based fractional Fourier transform. (February 2021) - Faragallah, Osama S.; El-sayed, Hala S.; Afifi, Ashraf; El-Shafai, Walid
Highlights: An effective and secure opto color image cryptosystem using 2D fractional Fourier transform (2D FrFT) and 2D logistic mapping (2D LM) is introduced. The proposed opto 2D LM-based 2D FrFT color image cryptosystem employed two confusion stages in the time and optical-based 2D FrFT using the 2D LM for color RGB images. The encryption characteristics are enhanced by utilizing the 2D-FrFT angles and orders as extra encryption keys in addition to double random phase masks. The simulation results illustrated a superiority improvement in the proposed opto 2D LM-based 2D FrFT color image cryptosystem compared to the recent state-of-the-art related works. Abstract: Nowadays, secure multimedia applications become a hot research issue because of rapid evolution in the application of multimedia over the Internet and wireless communications networks. Several researchers have introduced many chaos-based encryption methods to achieve data robustness and security communication. But, there exist several issues encountered in those methods regarding their fragility against differential attacks, delayed throughput, and inadmissible data expansibility. From this perspective, the paper presents an effective and secure opto color image cryptosystem using 2D Fractional Fourier Transform (2D FrFT) and 2D logistic mapping (2D LM). The proposed opto 2D LM-based 2D FrFT color image cryptosystem employed two confusion stages in the time and optical-based 2D FrFT using the 2D LM for color RGB images. Initially, the 2D LM is employed to shuffle the pixel positions of the RGB plainimage. After that, the optical-based FrFT is employed on the 2D LM-based shuffled RGB image. The complex transformed RGB image is again shuffled using the 2D LM, and finally, optically transformed using the FrFT. Furthermore, the encryption characteristics are enhanced by utilizing the 2D-FrFT angles and orders as extra encryption keys in addition to double random phase masks. The proposed opto 2D LM-based 2D FrFT color image cryptosystem is tested through the known security key indicators such as visual inspecting, entropy testing, histogram testing, cipher quality measures, noise testing, computational time analysis, occlusion attack analysis, and differential testing. The simulation results illustrated a superiority improvement in the proposed opto 2D LM-based 2D FrFT color image cryptosystem compared to the recent state-of-the-art related works.